66.045.126 DEVELOPMENT OF AN ENERGY-SAVING TECHNOLOGICAL SYSTEM TO IMPROVE THE HEAT TREATMENT STAGE OF MILK - Tojibaev, Makhmudjon; Absalom, Khudayberdiyev (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In order to meet the demand of the population for agricultural products, the products are stored and processed. Part of the processing of milk and milk products is pasteurization. In this article, detailed information is provided about the thermal calculation of pasteurizer plates for heat treatment of dairy products, its improvement and energy-saving technological system. Plate pasteurizers used in large milk processing enterprises consist of several sections, raw milk is first heated in its raw state for separation, and then directed to homogenization. After homogenization, it returns to the pasteurizer and is heated and pasteurized at the required temperature in the heating section. But in small milk processing enterprises, separation and homogenization are carried out separately, since such a complex system is expensive and requires a lot of energy. therefore, the sections of the plate pasteurizer consist of 3 types of cooling, recuperation and heating, and adjusting the output temperature of milk causes some difficulties. In this article, the problem of improvement of pasteurizer with plates used in small-scale milk processing enterprises is highlighted.